A Community-Based Assessment of Knowledge and Practice of Breast Self-Examination and Prevalence of Breast Disease in Southwest Cameroon. (1st January 2019) - Azemfac, Kareen; Christie, S. Ariane; Carvalho, Melissa M.; Nana, Theophile; Fonje, Ahmed N.; Halle-Ekane, Gregory; Dicker, Rochelle; Chichom-Mefire, Alain; Juillard, Catherine
Abstract : Introduction . Despite the rising trend in breast cancer incidence and mortality across Sub-Saharan Africa, there remains a critical knowledge gap about the burden and patterns of breast disease and breast cancer screening practices at the population level. This study aimed to identify socioeconomic factors associated with knowledge and practice of breast self-examination (BSE) as well as assess the prevalence of breast disease symptoms among a mixed urban-rural population of women in the Southwest region of Cameroon. Methods . We conducted a household-level community-based study in Southwest Cameroon between January and March 2017, using a three-stage cluster sampling framework. We surveyed 1287 households and collected self-reported data on 4208 female subjects, 790 of whom were household representatives. Each household representative provided information on behalf of all female household members about any ongoing breast disease symptoms. Moreover, female household representatives were questioned about their own knowledge and practice of BSE. Results . Women demonstrated low frequency of knowledge of BSE, as 25% (n=201) of household representatives reported any knowledge of BSE; and among these only 15% (n=30) practiced BSE on a monthly basis. Age (aOR: 1.04), usage of Liquid Petroleum Gas fuel, a marker of higher socioeconomic status (aOR: 1.86), and speaking English as a primary language in the household (aOR: 1.59) were significant predictors of knowledge of BSE. Eleven women reported ongoing breast disease symptoms resulting in an overall prevalence of 2.3 cases of breast disease symptoms per 1000 women. Conclusions . Socioeconomic disparities in access to health education may be a determinant of knowledge of BSE. Community-based strategies are needed to improve dissemination of breast cancer screening methods, particularly for women who face barriers to accessing care.